"They Ought to Know the Achievements of the Ancient Greeks": the Views of Greek Prospective Teachers on the Educational Role of Archaeology. (1st December 2017) - Kasvikis, Kostas
This paper focus on the role of archaeology and material culture in supporting national narratives for younger generations, examining the ideas and perceptions of prospective teachers of Greek Primary Education. Firstly, the contribution of archaeology to Greek society and its impact on Greek formal and informal education will be discussed briefly. Then, the quantitative and qualitative results of a research based on a detailed and extended questionnaire will be presented. The sample includes the opinions of 530 pre-graduate students attending Departments of Primary Education in Greece and focuses on their: perceptions about: the meanings of archaeology to Greek society; background concerning the consumption of archaeological knowledge; ideas about the role of material culture on their national, local and supranational identity; attitudes towards presenting archaeology in Primary School; mythical and distorted perceptions of various aspects of the past dealing with material culture. The research intends to provide evidentially based insights on the role of material culture as an important source of historical knowledge for young people, as a medium for constructing their narratives about the past and as appropriate knowledge to be taught at school. The study is part of a broader survey on the role of archaeology in Greek education conducted in the framework of the European funded project NEARCH (New scenarios for a community involved archaeology).